Optimal Spirituality Counseling Approach: Integration of Ritual, Theistic and Existential Values in Counseling Practices in Indonesia - Novitasari, Yuni; Noor, Marzuki; Dahlan, Syarifuddin (Sociometry Journal of Social Science, Art and Humanity, 2024)
Spirituality counseling has developed as a significant approach to supporting the mental health and well-being of individuals, especially in Indonesia, which has rich religious and cultural diversity. This research aims to develop and test a framework for an optimal spirituality counseling approach appropriate to the Indonesian context, focusing on integrating three main dimensions of spirituality: ritual, theistic, and existential. Data was collected using a quantitative survey method, the Daily Spirituality Preference Questionnaire (PSS), adapted to Indonesian society's cultural and religious conditions. The research results show that a balanced and integrated spirituality can positively impact solving problems and improving individual well-being. This study offers a solid theoretical framework and practical implications for counselors in implementing adaptive and holistic spirituality counseling. Recommendations for counseling practice in Indonesia include the importance of adapting interventions to the client's spiritual and cultural background and developing counselor competence in dealing with spiritual issues.